Implementasi Program Probebaya terhadap Pembangunan di Kecamatan Sungai Kunjang Kota Samarinda - Hariyana, Lilis; Tarmiji, Muhammad Rachmadani; Paselle, Enos (MES Management Journal, 2024)
The purpose of this study was to ascertain how the probebaya development program was implemented in Samarinda City's Sungai Kunjang District. Descriptive qualitative research is the type of this study. The information assortment strategies utilized are purposive examining and unplanned inspecting. Research on Tori Marilee S's policy implementation indicators is used to evaluate the Probebaya Program's development implementation in Samarinda City's Sungai Kunjang District. Grindle, specifically the policy's content and setting in which it will be implemented. This study's findings demonstrate that the implementation of the probebaya program is crucial to efforts to develop and improve the RT environment, particularly in relation to the existing infrastructure. The community is very aware of the program's advantages, which are significant. Through citizen consultation, decision-making is completely left to the community, and the community is heavily involved in its implementation by paying close attention to the relevant rules and regulations.